(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
The content of organic carbon is one of the essential factors that define soil quality. It is also notoriously challenging to model due to a multitude of biological and abiotic factors influencing the process. In this study, we investigate how decomposition of soil organic matter is affected by soil moisture and temperature. Soil organic carbon turnover is simulated by the CENTURY model. The accuracy of soil moisture data used is ensured by data assimilation approach, combing mathematical model and satellite retrievals. Numerical experiments demonstrate the influence of soil moisture regimes and climate on the quantity of soil humus stocks.